2021
DOI: 10.1080/21645515.2020.1859321
|View full text |Cite
|
Sign up to set email alerts
|

The adjuvanted recombinant zoster vaccine is efficacious and safe in Asian adults ≥ 50 years of age: a sub-cohort analysis of the ZOE-50 and ZOE-70 randomized trials

Abstract: In two large clinical trials (ZOE-50 [NCT01165177] and ZOE-70 [NCT01165229]), two doses of the adjuvanted recombinant zoster vaccine (RZV) demonstrated >90% efficacy (VE) against herpes zoster (HZ) in adults ≥50 years of age (YOA). This post-hoc analysis assessed the VE against HZ and postherpetic neuralgia (PHN), in participants from Asian study sites enrolled in ZOE-50/70. Reactogenicity and safety were also assessed. Participants ≥50 YOA were randomized 1:1 to receive 2 doses of either RZV or placebo, 2 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“… 21 In Asian populations ⩾50 years of age, RZV has an acceptable safety profile, similar to what was observed in the general ZOE-50/70 populations. 26 …”
Section: Pooled Analysis Of Two Pivotal Phase-3 Trials In Older Adultsmentioning
confidence: 99%
“… 21 In Asian populations ⩾50 years of age, RZV has an acceptable safety profile, similar to what was observed in the general ZOE-50/70 populations. 26 …”
Section: Pooled Analysis Of Two Pivotal Phase-3 Trials In Older Adultsmentioning
confidence: 99%
“…The general population has a lifetime risk of developing HZ of approximately 30%; this risk increases rapidly in adults older than 50 years of age. 26 Two clinical trials showed high efficacy of RZV against HZ, 7 , 8 with post-hoc analyses demonstrating similar efficacy in the subgroup of Asian subjects 18 and across geographic regions and ethnic groups. 27 The vaccine was licensed for use in the U.S. and China in the general population aged ≥50 years.…”
Section: Discussionmentioning
confidence: 97%
“… 17 However, the RZV clinical trials included Asian countries, and a post-hoc analysis of vaccine efficacy was conducted in Asian adults, which demonstrated similar efficacy as the overall study. 18 Recently, a post-licensure trial in China found a vaccine efficacy against HZ of 100% in adults aged ≥50 years. Although there are data on vaccine efficacy in Chinese adults, there are no real-world effectiveness data in Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
“… 37 , 38 Additionally, there was no variation in RZV vaccine efficacy by ethnicity in the Asian population, confirmed by an Asian subgroup analysis of global ZOE-50 and ZOE-70 trial data. 52 …”
Section: Methodsmentioning
confidence: 99%